Social Media Perception Affecting the Business of PTT Public Company Limited - Chatchalermpol, Achara; Pongsuwan, Wuttipong; Vajropala, Leelavadee (Information Management and Business Review, 2016)
The social media perception affecting the business of PTT Public Company Limited (PTT) aims for three purposes. Firstly, to study customersâ€™ behavior via social mediaâ€™s perception. Secondly, to study interaction between social media and customers. Finally, to study the impact of any information channels via social media that affects to user of products, related services, and companyâ€™s images. Social media has been played a vital role rapidly in communication and transferring a huge of information in the manner of videos and contents widespread, which persuade many companies to promote their company via social media to acquire customersâ€™ attentions even related services including the public relation for the companyâ€™s image. PTT has adjusted to a new era of social media comply with organizational communication plan. However, social media has affects both positive and negative impact at the same time. The company is rumored a negative issue in society and triggered by social media such as FBâ€™s page â€œPay back PTTâ€ is a web page for whom anti PTT. The company must handle these impact of negative information that can transfer to the customer of company in term of goods and service or any attitude that affect to companyâ€™s image after receiving any information that derived from social media. Therefore, it is necessary to manage social media contents to create two ways of understanding about any issues and also prevent social media disaster from companyâ€™s communication in term of attitude, image and decision making process to consume goods and service. This study is to provide recommended policy for PTT to improve their communication process and enhance trust for customer and investor in the future.